Medical polymer collagen polypeptide patch and manufacturing method thereof

CN120837729BActive Publication Date: 2026-10-09ZHONGJIA BAIKANG (FUJIAN) MEDICAL DEVICE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511162571.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2026-10-09
Estimated Expiration
2045-08-19

AI Technical Summary

Technical Problem

传统单一组分材料难以同时满足上述要求,而多组分复合材料的设计成为突破技术瓶颈的关键方向

Benefits of technology

[0028] I. This invention achieves a dual breakthrough in material biocompatibility and mechanical properties through multi-component synergistic design. It combines type I collagen with medical-grade polypropylene and introduces nano-hydroxyapatite as a bioactive filler. The needle-like structure of nano-hydroxyapatite significantly improves the osteoconductive properties of the material, while the medical-grade molecular weight design of polypropylene ensures long-term stability after implantation. Through biocompatibility interface modification technology, polypropylene particles are ultrasonically treated in an ethanol solution containing 5-8% collagen hydrolysate peptides, which effectively reduces the immunogenicity of the material surface. In addition, the co-blending toughening process of silk fibroin improves tensile strength while maintaining the flexibility of the patch, and at the same time, solves the problem of easy cracking of traditional adhesive raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120837729B_ABST
    Figure CN120837729B_ABST
Patent Text Reader

Abstract

The application discloses a medical polymer collagen polypeptide patch and a manufacturing method thereof, and relates to the technical field of medical materials. The polypeptide patch comprises the following raw materials in parts by weight: collagen protein: 50-70; polypropylene: 30-50; nano-hydroxyapatite: 2-5; silk fibroin: 5-8; and immune regulatory factor: 0.1-0.5. The application realizes a double breakthrough of material biocompatibility and mechanical property through multi-component synergistic design. Type I collagen protein is compounded with medical-grade polypropylene, and nano-hydroxyapatite is introduced as a bioactive filler. The needle-like structure of the nano-hydroxyapatite significantly improves the bone conduction property of the material, and the medical-grade molecular weight design of the polypropylene ensures the stability after long-term implantation. Through a biocompatibility interface modification technology, the polypropylene particles are placed in an ethanol solution containing 5-8% collagen protein hydrolysis peptides and are subjected to ultrasonic treatment, so that the immunogenicity of the surface of the material is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical materials technology, specifically to a medical polymer collagen polypeptide patch and its manufacturing method. Background Technology

[0002] Biomedical materials, as a core support of modern medical technology, directly determine the clinical efficacy of tissue repair and regenerative medicine. In recent years, with the increasing aging population and the rise in traumatic diseases, the market demand for implantable materials that combine bioactivity, mechanical adaptability, and functional controllability has surged. In orthopedics, bone defect repair requires materials that simultaneously possess osteoconductive properties, osteoinductive properties, and the ability to match the host bone degradation rate. In general surgery, abdominal wall hernia repair materials need to maintain structural integrity under dynamic stress conditions while avoiding the induction of chronic inflammation. Traditional single-component materials cannot simultaneously meet these requirements, making the design of multi-component composite materials a key direction for overcoming technological bottlenecks.

[0003] Current medical patch technology suffers from several shortcomings: First, the material composition is limited. While synthetic polymers offer excellent mechanical properties, they lack bioactivity, easily leading to fibrosis of surrounding tissues after implantation and affecting long-term repair outcomes. Natural polymers, though biocompatible, lack sufficient mechanical strength and are prone to breakage at dynamically stressed sites. Second, interfacial bonding technology is outdated. Traditional physical blending or coating processes result in weak interfacial bonding between the filler and the matrix, making filler detachment during use and triggering local inflammatory reactions. Third, functional design is lacking. Most patches serve only as passive support structures and cannot actively regulate the postoperative inflammatory microenvironment, and excessive postoperative inflammatory responses are a major factor leading to implantation failure. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a medical polymer collagen polypeptide patch and its manufacturing method. By combining type I collagen, medical-grade polypropylene, nano-hydroxyapatite and silk fibroin, and introducing interleukin-10 immunomodulatory factor, the synergistic optimization of biocompatibility, mechanical strength and active immune regulation function is achieved.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: In one aspect, a medical polymeric collagen polypeptide patch, wherein the polypeptide patch comprises, by weight, the following raw materials:

[0006] Collagen: 50-70;

[0007] Polypropylene: 30-50;

[0008] Nano-hydroxyapatite: 2-5;

[0009] Silk fibroin: 5-8;

[0010] Immunomodulatory factors: 0.1-0.5.

[0011] Furthermore, the collagen is type I collagen, extracted from animal skin or tendon tissue, with a molecular weight of 300,000 to 500,000 Da and a hydroxyproline content of ≥10%.

[0012] Furthermore, the polypropylene resin is medical grade, with a molecular weight of 200,000 to 300,000 and a melt index of 2 to 5 g / 10 min.

[0013] Furthermore, the nano-hydroxyapatite is needle-shaped or rod-shaped crystal with a particle size of 20 to 50 nm, an aspect ratio of 5:1 to 10:1, and a purity of ≥99%.

[0014] Furthermore, the silk fibroin is extracted from silkworm cocoons and prepared through degumming, dissolving, and dialysis processes, with a molecular weight of 100,000 to 300,000.

[0015] Furthermore, the immunomodulatory factor is interleukin-10, with a purity ≥95% and an activity ≥1×10⁻⁶. 6 U / mg.

[0016] On the other hand, a method for manufacturing a medical polymer collagen polypeptide patch includes the following steps:

[0017] Biocompatibility interface modification: Polypropylene resin particles were placed in a 75% ethanol solution containing collagen hydrolysate peptides, sonicated for 20 to 30 minutes, and then dried.

[0018] In-situ doping of nano-hydroxyapatite: Nano-hydroxyapatite is mixed with collagen powder, dispersed by high-speed shearing for 5 to 10 minutes, and then mixed with polypropylene particles after the biocompatibility interface modification step.

[0019] Silk fibroin blending and toughening: Silk fibroin was added to the mixture obtained by the in-situ doping step of nano-hydroxyapatite and stirred at a rate of 200 to 500 rpm for 30 to 40 min.

[0020] Melt spinning: The mixed raw material obtained from the silk fibroin blending and toughening step is vacuum dried to a moisture content of ≤2%, and then spun at 180 to 200°C to produce a mixed yarn with a diameter of 50 to 100 μm;

[0021] Enzyme-catalyzed in-situ cross-linking: The mixed threads are immersed in a transglutaminase solution and reacted at 35 to 40°C for 1 to 3 hours, controlling the degree of cross-linking to 50% to 80%;

[0022] Introducing immunomodulatory factors: The cross-linked mixed thread was immersed in interleukin-10 solution, left to stand at 4°C for 12 to 24 hours, and then dried.

[0023] Weaving into patches: The mixed yarn is woven into patches with a stitch pitch of 0.5 to 1 mm and a weaving density of 20 to 30 stitches / cm², and then packaged after being sterilized by gamma irradiation.

[0024] Furthermore, in the biocompatible interface modification, the mass concentration of collagen hydrolysate peptides in the ethanol solution is 5 to 8%; after ultrasonic treatment, the polypropylene particles are rinsed 2 to 3 times with anhydrous ethanol and dried to constant weight in a vacuum drying oven at 40 to 50°C.

[0025] Furthermore, in the melt spinning process, the melt spinning parameters are: screw speed 30 to 50 rpm, spinneret orifice diameter 0.1 to 0.3 mm, and winding speed 500 to 800 m / min.

[0026] Furthermore, in the enzyme-catalyzed in-situ cross-linking process, a transglutaminase solution with a concentration of 2 to 5 U / mL is prepared using phosphate buffer; in the introduction of the immunomodulatory factor, the immunomodulatory factor is interleukin-10, prepared using physiological saline to a concentration of 0.01 to 0.05 mg / mL; in the weaving into a patch, gamma irradiation is performed using... 60 Co radiation source, dose 25 to 30 kGy.

[0027] Compared with existing technologies, this medical polymer collagen polypeptide patch and its manufacturing method have the following beneficial effects:

[0028] I. This invention achieves a dual breakthrough in material biocompatibility and mechanical properties through multi-component synergistic design. It combines type I collagen with medical-grade polypropylene and introduces nano-hydroxyapatite as a bioactive filler. The needle-like structure of nano-hydroxyapatite significantly improves the osteoconductive properties of the material, while the medical-grade molecular weight design of polypropylene ensures long-term stability after implantation. Through biocompatibility interface modification technology, polypropylene particles are ultrasonically treated in an ethanol solution containing 5-8% collagen hydrolysate peptides, which effectively reduces the immunogenicity of the material surface. In addition, the co-blending toughening process of silk fibroin improves tensile strength while maintaining the flexibility of the patch, and at the same time, solves the problem of easy cracking of traditional adhesive raw materials.

[0029] II. This invention achieves dynamic regulation of material function through enzymatic in-situ cross-linking and precise introduction of immunomodulatory factors. Transglutaminase is used to catalyze collagen cross-linking at 35-40℃, with the degree of cross-linking controlled at 50-80%. This ensures the structural stability of the material while avoiding the loss of biological activity caused by excessive cross-linking. More importantly, by loading interleukin-10 into the material at a concentration of 0.01-0.05 mg / mL, the patch is endowed with the ability to actively regulate inflammatory responses. The optimization of its weaving process further improves the integration efficiency between the material and the host tissue. Combined with gamma-ray irradiation sterilization technology, the sterility and long-term storage stability of the product are ensured.

[0030] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0032] Figure 1 A flowchart illustrating the steps involved in the fabrication of a medical polymer collagen polypeptide patch.

[0033] Figure 2 This is a flowchart illustrating the manufacturing process of medical polymer collagen peptide patches. Detailed Implementation

[0034] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.

[0035] Example 1

[0036] Examples of medical polymer collagen peptide patches

[0037] I. Raw material preparation (by weight).

[0038] Collagen: 60 parts (Type I, extracted from bovine tendon, molecular weight 400,000 Da, hydroxyproline content 12%), which provides a natural matrix for cell growth in abdominal wall defects and can promote cell adhesion and tissue regeneration.

[0039] Polypropylene: 40 parts (medical grade, molecular weight 250,000, melt index 3.5g / 10min), used as a mechanical support framework for the patch, can enhance tensile strength and morphological stability, and prevent abdominal wall tearing due to abdominal pressure after repair.

[0040] Nano-hydroxyapatite: 3 parts (needle-shaped crystals, 30nm particle size, aspect ratio 7:1, purity 99.5%), mimicking the inorganic components of the bone and soft tissue interface, can enhance bioactivity, promote tissue mineralization and integration in defective areas, and increase hardness.

[0041] Silk fibroin: 6 parts (extracted from silkworm cocoons, degummed, dissolved, and dialyzed, molecular weight 200,000), can improve the flexibility and extensibility of the patch, reduce the brittleness of polypropylene, and make the patch fit the needs of abdominal wall tissue movement better.

[0042] Immunomodulatory factors: 0.3 parts (interleukin-10, purity 96%, activity 1.2×10⁻⁶) 6 U / mg can inhibit excessive inflammatory response at the abdominal wall defect site, reduce the risk of postoperative rejection, and promote the balance of the immune microenvironment to accelerate healing.

[0043] II. Production steps, as follows Figure 1 As shown.

[0044] Biocompatibility interface modification: 40 parts of polypropylene resin particles were placed in a 75% ethanol solution containing 5% collagen hydrolysed peptides, sonicated for 25 min, rinsed 3 times with anhydrous ethanol, and dried to constant weight in a vacuum drying oven at 45℃. This step uses ultrasound to allow the collagen hydrolysed peptides to be uniformly adsorbed on the surface of polypropylene particles, improving the interfacial compatibility between the hydrophobicity of polypropylene and the hydrophilicity of collagen, avoiding uneven mixing caused by polarity differences, and laying a stable foundation for subsequent blending.

[0045] In-situ doping of nano-hydroxyapatite: 3 parts nano-hydroxyapatite were mixed with 60 parts collagen powder and dispersed by high-speed shearing at 3000 rpm for 8 min. Then, it was mixed with the polypropylene particles treated in step 1. High-speed shearing made the nano-hydroxyapatite uniformly dispersed in the collagen matrix to prevent agglomeration. In-situ doping allowed the nanoparticles to bind tightly with the collagen, enhancing the bioactivity and mechanical strength of the patch, while providing cells with a microenvironment similar to natural bone tissue.

[0046] Silk fibroin blending for toughening: Add 6 parts of silk fibroin to the mixing system in step 2 and stir at 350 rpm for 35 min. The silk fibroin molecular chains form an interpenetrating network structure with collagen and polypropylene. The intermolecular forces enhance the toughness of the mixing system, making the patch less prone to breakage and maintaining a certain elasticity when subjected to abdominal wall contraction force.

[0047] Melt spinning: The mixed raw materials from step 3 are vacuum dried to a moisture content of 1.5%, and spun at 190°C (screw speed 40 rpm, spinneret orifice diameter 0.2 mm, winding speed 650 m / min) to produce a mixed yarn with a diameter of 75 μm. Melt spinning forms a continuous fiber yarn. The 75 μm diameter simulates the diameter of natural abdominal wall tissue fibers, which is convenient for subsequent weaving. The moisture content and spinning temperature are strictly controlled to avoid moisture causing yarn breakage during spinning, while ensuring that polypropylene is fully melted and uniformly combined with other components.

[0048] Enzyme-catalyzed in-situ cross-linking: The mixed thread was immersed in a 3 U / mL transglutaminase solution prepared with phosphate buffer and reacted at 37°C for 2 hours. The degree of cross-linking was controlled at 65%. Transglutaminase catalyzes the formation of covalent bonds between the amino and carboxyl groups of collagen and silk fibroin, which improves the degradation resistance and mechanical stability of the mixed thread and avoids premature enzymatic degradation of the patch in vivo. The 65% degree of cross-linking balances the degradation rate and the tissue regeneration rate.

[0049] Introducing immunomodulatory factors: The cross-linked hybrid thread was immersed in a 0.03 mg / mL interleukin-10 solution prepared with physiological saline, left to stand at 4°C for 18 hours, dried, and left to stand at low temperature to reduce the loss of interleukin-10 activity, so that it was evenly adsorbed on the surface and pores of the hybrid thread, and slowly released after implantation, continuously inhibiting the inflammatory response and reducing the risk of postoperative abdominal wall tissue swelling and rejection.

[0050] Knitting into a patch: Knit the mixed yarn into a patch with a stitch length of 0.8mm and a knitting gauge of 25 stitches / cm². 60 Sterilized by Co radiation source (dose 28 kGy) before packaging, specific needle spacing and weaving density ensure an appropriate porosity of approximately 50% for the patch, allowing cell migration and blood vessel ingrowth. Gamma-ray irradiation thoroughly kills bacteria and viruses without damaging the patch's chemical structure and biological activity, ensuring safe clinical use. Figure 2 As shown.

[0051] III. Conclusion.

[0052] The medical polymer collagen peptide patch prepared in this embodiment has a tensile strength of 16.8 MPa and an elongation at break of 35%, which meets the mechanical requirements for abdominal wall repair. Cell compatibility experiments show that the cell adhesion rate on the patch surface reaches 92%, and the proliferation rate is 30% higher than that of traditional patches. These data indicate that the patch has good mechanical properties, biocompatibility, and tissue repair effects, and has clinical application value.

[0053] Example 2:

[0054] Detailed explanation of different collagen dosages.

[0055] This embodiment is based on the framework of Example 1, only adjusting the amount of collagen (50 parts, 55 parts, 60 parts, 65 parts, and 70 parts respectively, all within the specified range of 50-70 parts by weight). The amounts of other raw materials, production steps, and process parameters remain the same, as follows:

[0056] I. Raw material preparation (by weight).

[0057] Collagen: 50 parts, 55 parts, 60 parts, 65 parts, and 70 parts (all type I, extracted from bovine tendon, molecular weight 400,000 Da, hydroxyproline content 12%).

[0058] Polypropylene: 40 parts (medical grade, molecular weight 250,000, melt index 3.5 g / 10 min);

[0059] Nano-hydroxyapatite: 3 parts (acicular crystals, particle size 30nm, aspect ratio 7:1, purity 99.5%).

[0060] Silk fibroin: 6 parts (extracted from silkworm cocoons, after degumming, dissolving, and dialysis, molecular weight 200,000);

[0061] Immunomodulatory factors: 0.3 parts (interleukin-10, purity 96%, activity 1.2×10⁻⁶) 6 U / mg).

[0062] II. Production steps (completely consistent with Example 1).

[0063] Biocompatibility interface modification: 40 parts of polypropylene resin particles were placed in a 75% ethanol solution containing 5% collagen hydrolysate peptides, sonicated for 25 min, rinsed 3 times with anhydrous ethanol, and dried to constant weight in a vacuum drying oven at 45℃.

[0064] In-situ doping of nano-hydroxyapatite: 3 parts of nano-hydroxyapatite were mixed with different amounts of collagen powder, dispersed by high-speed shearing at 3000 rpm for 8 min, and then mixed with polypropylene particles treated in step 1.

[0065] Silk fibroin blending and toughening: Add 6 parts of silk fibroin to the mixing system in step 2 and stir at 350 rpm for 35 min;

[0066] Melt spinning: The mixed raw materials from step 3 are vacuum dried to a moisture content of 1.5%, and spun at 190°C (screw speed 40 rpm, spinneret orifice diameter 0.2 mm, winding speed 650 m / min) to produce a mixed yarn with a diameter of 75 μm;

[0067] Enzyme-catalyzed in-situ cross-linking: The mixed thread was immersed in a 3 U / mL transglutaminase solution prepared with phosphate buffer and reacted at 37°C for 2 h, with the degree of cross-linking controlled at 65%;

[0068] Introducing immunomodulatory factors: The cross-linked mixed thread was immersed in a 0.03 mg / mL interleukin-10 solution prepared with physiological saline, stood at 4°C for 18 h, and then dried;

[0069] Knitting into a patch: Knit the mixed yarn into a patch with a stitch length of 0.8mm and a knitting gauge of 25 stitches / cm². 60 Sterilized by Co radiation source (dose 28kGy) before packaging.

[0070] III. Performance Test Results.

[0071] 50 18.2 30 85 22 Good match (degradation is slightly slower) 55 17.5 32 88 25 match 60 16.8 35 92 30 Best match 65 16.2 38 90 28 match 70 15.5 40 86 24 Good match (degrades slightly faster)

[0072] In summary, as shown in the table above, at 50 parts by weight of collagen, the patch exhibits the highest tensile strength and strong mechanical support, but lower cell adhesion and proliferation rates, and degradation is slightly slower than tissue regeneration, making it suitable for hard tissue repair with high mechanical performance requirements. At 55 parts by weight, mechanical performance and bioactivity tend to be balanced, and the degradation rate is synchronized with tissue regeneration, making it suitable for soft tissue repair under moderate stress. At 60 parts by weight, overall performance is optimal, with good flexibility and cell compatibility, and the highest degree of matching between degradation and regeneration, making it suitable for most abdominal wall and tendon repair scenarios. At 65 parts by weight, flexibility is further improved, and bioactivity remains at a high level, making it suitable for repairing dynamically stressed areas. At 70 parts by weight, flexibility is best, but tensile strength is lowest, and degradation is slightly faster, making it suitable for repairing superficial tissues under low stress. Therefore, a collagen dosage within the range of 50-70 parts by weight can achieve a dynamic balance in patch performance, with 60 parts being the optimal choice.

[0073] Example 3:

[0074] Different amounts of polypropylene.

[0075] This embodiment is based on Example 1, only adjusting the amount of polypropylene (30 parts, 35 parts, 40 parts, 45 parts, and 50 parts respectively, all within the specified range of 30-50 parts by weight), while the amount of other raw materials and the production steps are the same as in Example 1.

[0076] I. Raw material preparation (by weight).

[0077] Collagen: 60 parts (Type I, extracted from bovine tendon, molecular weight 400,000 Da, hydroxyproline content 12%)

[0078] Polypropylene: 30 parts, 35 parts, 40 parts, 45 parts, 50 parts (medical grade, molecular weight 250,000, melt index 3.5g / 10min);

[0079] Nano-hydroxyapatite: 3 parts (acicular crystals, particle size 30nm, aspect ratio 7:1, purity 99.5%).

[0080] Silk fibroin: 6 parts (extracted from silkworm cocoons, after degumming, dissolving, and dialysis, molecular weight 200,000);

[0081] Immunomodulatory factors: 0.3 parts (interleukin-10, purity 96%, activity 1.2×10⁻⁶) 6 U / mg).

[0082] II. Production steps (completely consistent with Example 1).

[0083] Biocompatibility interface modification: Polypropylene resin particles of different amounts were placed in a 75% ethanol solution containing 5% collagen hydrolysate peptides, sonicated for 25 min, rinsed 3 times with anhydrous ethanol, and dried to constant weight in a vacuum drying oven at 45℃.

[0084] In-situ doping of nano-hydroxyapatite: 3 parts of nano-hydroxyapatite were mixed with 60 parts of collagen powder and dispersed at high speed of 3000 rpm for 8 min, and then mixed with polypropylene particles treated in step 1.

[0085] Silk fibroin blending and toughening: Add 6 parts of silk fibroin to the mixing system in step 2 and stir at 350 rpm for 35 min;

[0086] Melt spinning: The mixed raw materials from step 3 are vacuum dried to a moisture content of 1.5%, and spun at 190°C (screw speed 40 rpm, spinneret orifice diameter 0.2 mm, winding speed 650 m / min) to produce a mixed yarn with a diameter of 75 μm;

[0087] Enzyme-catalyzed in-situ cross-linking: The mixed thread was immersed in a 3 U / mL transglutaminase solution prepared with phosphate buffer and reacted at 37°C for 2 h, with the degree of cross-linking controlled at 65%;

[0088] Introducing immunomodulatory factors: The cross-linked mixed thread was immersed in a 0.03 mg / mL interleukin-10 solution prepared with physiological saline, stood at 4°C for 18 h, and then dried;

[0089] Knitting into a patch: Knit the mixed yarn into a patch with a stitch length of 0.8mm and a knitting gauge of 25 stitches / cm². 60 Sterilized by Co radiation source (dose 28kGy) before packaging.

[0090] III. Comparison of the effects of polypropylene dosage on medical polymer collagen peptide patches.

[0091] 30 14.5 42 93 32 generally 35 15.6 39 92 31 good 40 16.8 35 92 30 Excellent 45 18.0 32 89 27 Excellent 50 19.2 28 86 24 Excellent

[0092] In summary, as shown in the table above, the use of polypropylene in the range of 30-50 parts by weight has a significant impact on patch performance: with increasing dosage, tensile strength gradually increases, long-term stability is enhanced, and the requirements of different stress scenarios are met; elongation at break decreases slightly, but good flexibility is still maintained; cell adhesion rate and proliferation rate are higher at 30-40 parts, with good biocompatibility, while they decrease slightly above 40 parts due to the increased proportion. Overall, the use of polypropylene in this range can balance the mechanical properties, biocompatibility, and stability of the patch, with 40 parts showing the best comprehensive performance, providing reliable mechanical support and ensuring good tissue repair effects, which meets the clinical needs of medical patches.

[0093] Example 4:

[0094] Dosage of different immunomodulatory factors.

[0095] This embodiment is based on Example 1, only adjusting the dosage of the immunomodulatory factor (interleukin-10) (0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, and 0.5 parts respectively, all within the specified range of 0.1-0.5 parts by weight). The dosage of other raw materials and the preparation steps are consistent with Example 1.

[0096] I. Raw material preparation (by weight).

[0097] Collagen: 60 parts (Type I, extracted from bovine tendon, molecular weight 400,000 Da, hydroxyproline content 12%)

[0098] Polypropylene: 40 parts (medical grade, molecular weight 250,000, melt index 3.5 g / 10 min);

[0099] Nano-hydroxyapatite: 3 parts (acicular crystals, particle size 30nm, aspect ratio 7:1, purity 99.5%).

[0100] Silk fibroin: 6 parts (extracted from silkworm cocoons, after degumming, dissolving, and dialysis, molecular weight 200,000);

[0101] Immunomodulatory factors: 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts (interleukin-10, purity 96%, activity 1.2×10⁻⁶) 6 U / mg).

[0102] II. Production steps (completely consistent with Example 1).

[0103] Biocompatibility interface modification: 40 parts of polypropylene resin particles were placed in a 75% ethanol solution containing 5% collagen hydrolysate peptides, sonicated for 25 min, rinsed 3 times with anhydrous ethanol, and dried to constant weight in a vacuum drying oven at 45℃.

[0104] In-situ doping of nano-hydroxyapatite: 3 parts of nano-hydroxyapatite were mixed with 60 parts of collagen powder and dispersed at high speed of 3000 rpm for 8 min, and then mixed with polypropylene particles treated in step 1.

[0105] Silk fibroin blending and toughening: Add 6 parts of silk fibroin to the mixing system in step 2 and stir at 350 rpm for 35 min;

[0106] Melt spinning: The mixed raw materials from step 3 are vacuum dried to a moisture content of 1.5%, and spun at 190°C (screw speed 40 rpm, spinneret orifice diameter 0.2 mm, winding speed 650 m / min) to produce a mixed yarn with a diameter of 75 μm;

[0107] Enzyme-catalyzed in-situ cross-linking: The mixed thread was immersed in a 3 U / mL transglutaminase solution prepared with phosphate buffer and reacted at 37°C for 2 h, with the degree of cross-linking controlled at 65%;

[0108] Introducing immunomodulatory factors: The cross-linked mixed threads were immersed in interleukin-10 solutions of corresponding concentrations (prepared according to dosage), stood at 4°C for 18 hours, and then dried;

[0109] Knitting into a patch: Knit the mixed yarn into a patch with a stitch length of 0.8mm and a knitting gauge of 25 stitches / cm². 60 Sterilized by Co radiation source (dose 28kGy) before packaging.

[0110] III. Comparative Table of the Effects of Immunomodulatory Factor Dosage on the Performance of Medical Polymer Collagen Peptide Patches

[0111] 0.1 65 15 18 10 0.1 0.2 78 8 15 15 0.2 0.3 85 3 12 20 0.3 0.4 84 4 13 19 0.4 0.5 82 5 14 18 0.5

[0112] In summary, the table above shows that within the dosage range of 0.1-0.5 parts by weight of immunomodulatory factors, their impact on the immunomodulatory function of the patch is significant: with increasing dosage, inflammation suppression initially increases and then stabilizes, the incidence of postoperative rejection decreases, tissue integration speed increases, and the duration of immune microenvironment balance is prolonged. At 0.3 parts, the overall performance is optimal, with an inflammation suppression rate of 85%, a rejection rate of only 3%, the fastest tissue integration (12 days), and the longest duration of balance maintenance (20 days). This dosage range can effectively exert the immunomodulatory effect, avoiding insufficient inflammation control due to too low a dosage or excessive immunosuppression due to too high a dosage, ensuring the safe and efficient repair of the patch in vivo, and meeting clinical needs for immune regulation.

[0113] Example 5:

[0114] Stability testing of medical polymer collagen peptide patches.

[0115] This embodiment uses the formula and manufacturing process of Example 1 as a basis to conduct long-term stability testing on the prepared medical polymer collagen peptide patch. The test sample is the patch prepared in Example 1, and the raw material dosage and production steps remain unchanged. Performance tests are conducted at storage days 0 (initial state), 30 days, 90 days, 180 days, and 365 days, as detailed below:

[0116] I. Test Samples and Conditions

[0117] Sample: The patch prepared in Example 1 (60 parts collagen, 40 parts polypropylene, 3 parts nano hydroxyapatite, 6 parts silk fibroin, 0.3 parts immunomodulatory factor);

[0118] Storage conditions: Sealed environment at 25℃ and relative humidity of 50%±5% (simulating normal storage conditions);

[0119] Test indicators: tensile strength, elongation at break, cell adhesion rate, retention rate of immunomodulatory factor activity, and sterility (after sterilization by gamma ray irradiation).

[0120] II. Comparison Table of Stability Test Results

[0121] 0 (Initial) 16.8 35 92 100 qualified 30 16.7 34 91 95 qualified 90 16.5 33 90 90 qualified 180 16.2 32 88 85 qualified 365 15.8 30 85 80 qualified

[0122] In summary, as shown in the table above, this embodiment demonstrates good stability of the medical polymer collagen peptide patch during different storage periods, based on stability testing. The patch exhibits good stability over a 365-day storage period. Data shows that all key performance indicators change slowly over time, but the decrease is relatively small: tensile strength decreased from an initial 16.8 MPa to 15.8 MPa at 365 days, a decrease of approximately 5.9%; elongation at break decreased from 35% to 30%, a decrease of approximately 14.3%; cell adhesion decreased from 92% to 85%, a decrease of approximately 7.6%; and immune regulation... The factor activity retention rate decreased from 100% to 80%, but it still maintained effective biological function. At the same time, the patch remained sterile throughout the entire storage period without microbial contamination. This indicates that the patch can maintain structural integrity, mechanical properties and biological activity for a long time under normal storage conditions, meeting the strict stability requirements of medical materials and providing reliable quality assurance for clinical applications. This demonstrates the rationality and effectiveness of the invention in material formulation design (such as the stability support of medical-grade polypropylene and the structural reinforcement of enzyme-catalyzed cross-linking) and sterilization process (γ-ray irradiation).

[0123] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A medical polymer collagen polypeptide patch, characterized in that, The polypeptide patch comprises the following ingredients by weight: Collagen: 50-70; Polypropylene: 30-50; Nano-hydroxyapatite: 2-5; Silk fibroin: 5-8; Immunomodulatory factors: 0.1-0.5; One of the specific manufacturing methods for a medical polymer collagen polypeptide patch is as follows: Biocompatibility interface modification: Polypropylene resin particles were placed in a 75% ethanol solution containing collagen hydrolysate peptides, sonicated for 20 to 30 minutes, and then dried. In-situ doping of nano-hydroxyapatite: Nano-hydroxyapatite is mixed with collagen powder, dispersed by high-speed shearing for 5 to 10 minutes, and then mixed with polypropylene particles after the biocompatibility interface modification step. Silk fibroin blending and toughening: Silk fibroin was added to the mixture obtained by the in-situ doping step of nano-hydroxyapatite and stirred at a rate of 200 to 500 rpm for 30 to 40 min. Melt spinning: The mixed raw material obtained from the silk fibroin blending and toughening step is vacuum dried to a moisture content of ≤2%, and then spun at 180 to 200°C to produce a mixed yarn with a diameter of 50 to 100 μm; Enzyme-catalyzed in-situ cross-linking: The mixed threads are immersed in a transglutaminase solution and reacted at 35 to 40°C for 1 to 3 hours, controlling the degree of cross-linking to 50% to 80%; Introducing immunomodulatory factors: The cross-linked mixed thread was immersed in interleukin-10 solution, left to stand at 4°C for 12 to 24 hours, and then dried. Weaving into patches: The mixed yarn is woven into patches with a stitch pitch of 0.5 to 1 mm and a weaving density of 20 to 30 stitches / cm², and then packaged after being sterilized by gamma irradiation.

2. The medical polymer collagen polypeptide patch according to claim 1, characterized in that, The collagen is type I collagen, extracted from animal skin or tendon tissue, with a molecular weight of 300,000 to 500,000 Da and a hydroxyproline content of ≥10%.

3. The medical polymer collagen polypeptide patch according to claim 1, characterized in that, The polypropylene resin is medical grade, with a molecular weight of 200,000 to 300,000 and a melt index of 2 to 5 g / 10 min.

4. The medical polymer collagen polypeptide patch according to claim 1, characterized in that, The nano-hydroxyapatite is a needle-like or rod-like crystal with a particle size of 20 to 50 nm, an aspect ratio of 5:1 to 10:1, and a purity of ≥99%.

5. A medical polymer collagen polypeptide patch according to claim 1, characterized in that, The silk fibroin is extracted from silkworm cocoons and prepared through degumming, dissolving, and dialysis processes, with a molecular weight of 100,000 to 300,000.

6. A medical polymer collagen polypeptide patch according to claim 1, characterized in that, The immunomodulatory factor is interleukin-10, with a purity ≥95% and an activity ≥1×10⁻⁶. 6 U / mg.

7. A medical polymer collagen polypeptide patch according to claim 1, characterized in that, In the biocompatible interface modification, the mass concentration of collagen hydrolysate peptides in the ethanol solution is 5 to 8%; after ultrasonic treatment, the polypropylene particles are rinsed 2 to 3 times with anhydrous ethanol and dried to constant weight in a vacuum drying oven at 40 to 50°C.

8. A medical polymer collagen polypeptide patch according to claim 1, characterized in that, In the melt spinning process, the parameters of melt spinning are: screw speed 30 to 50 rpm, spinneret orifice diameter 0.1 to 0.3 mm, and winding speed 500 to 800 m / min.

9. A medical polymer collagen polypeptide patch according to claim 1, characterized in that, In the enzyme-catalyzed in-situ cross-linking process, a transglutaminase solution with a concentration of 2 to 5 U / mL is prepared using phosphate buffer; in the introduction of the immunomodulatory factor, the immunomodulatory factor is interleukin-10, prepared using physiological saline to a concentration of 0.01 to 0.05 mg / mL; in the weaving into a patch, gamma irradiation is performed using... 60 Co radiation source, dose 25 to 30 kGy.

Citation Information

Patent Citations

  • Mesh-based in situ cross-linkable compositions

    CN109475400A

  • Composite stent for rotator cuff repair and preparation method thereof

    CN119971136A